Soil microbiological attributes under summer/winter crops rotation in a no-tillage system - Borges, Clovis Daniel [UNESP]; Cora, Jose Eduardo [UNESP]; Barbosa, Jose Carlos [UNESP]; Nahas, Ely [UNESP] (Taylor & Francis Ltd, 2013)
Knowledge of the effect of a multiple combination of summer/winter crop rotation on the microbiological properties of soil would allow a more adequate response to its use. This study aimed to evaluate the effect of the rotation of three summer crops (continuous soybean, continuous maize and soybean/maize rotation) in combination with seven winter crops (maize, sunflower, oilseed radish, millet, pigeon pea, sorghum and sunn hemp) on the microbiological properties of the soil. A soybean/maize (SM) rotation had a greater influence on microbial biomass than continuous maize (MM) and continuous soybean (SS). Urease and phosphatase activities were not affected by the crop rotation. Dehydrogenase activity was higher in continuous crops (MM and SS) than in SM, whereas respiratory activity was higher in SM than in continuous crops. For the SM rotation, the main variables selected by principal components analysis were microbial biomass C, N and P, respiratory and phosphatase activities, and microbial quotient. Pigeon pea, sorghum and sunn hemp had a greater effect on soil properties than the other winter crops. In general, the degree of influence of the summer and winter crops on the microbiological soil properties can be ranked as follows: SM>MM > SS, and millet>sorghum > sunn hemp>radish > pigeon pea>maize, respectively.
Keywords: Microbial biomass; multiple crop rotation; Soil enzyme; soil respiratory activity